Morpho-Physiological Responses of Soybean Varieties to Salinity Stress (Bangladesh Agronomy Journal, 2022)
Soybean (Glycine max L. Merr) has a tremendous value in agriculture as a good source of high-quality plant protein and vegetable oils in one hand and nitrogen fixing ability on the other, now a day largely growing in coastal salt marshes areas of Bangladesh. The aim of this study was to evaluate morphological and physiological responses of soybean varieties (Shohag, BARI Soybean-6, BARI Soybean-5 and Binasoybean-4) to pot grown plants in different concentrations of salinity level i.e., control (0.3), 4, 8 and 12 dS m−1 during 2020-21. Irrespective of the variety, with the increase of salinity levels physiological parameters as well as seed yield were greatly affected. Salinity stress decreased total chlorophyll (Chl a+b) and total dry matter (TDM) was reduced due to salinity stress, which ultimately reduced seed yield irrespective of the variety. Sodium (Na+), calcium (Ca2+), potassium (K+) ion content and the potassium sodium ratios (K+: Na+) in leaf tissue were significantly affected by salinity levels. Under salinity stress, BARI Soybean- 6 showed a higher K+: Na+ ratio in leaf, which indicates higher tolerance to salinity compared to others. However, H2O2 and MDA contents was comparatively lower in the respective variety. This variety also showed higher TDM production, filled pods plant-1 and seed yield plant-1 in all salinity levels compared to other varieties. Results revealed that, soybean var. BARI Soybean-6showedmore tolerance against salinity stress compared to other varieties.Bangladesh Agron. J. 2022, 25(1): 15-22